Designing an adoptable classification scheme for Hinduism based on Dewey decimal classification – a study - Arulanantham, S. (Prof. Piyadasa Ranasinghe Felicitation sovenir, 2014)
The main objective of this research is to develop an adoptable comprehensive and user oriented classification system for Hinduism within the DDC principles, for the libraries which use Dewey decimal classification to organise their materials, considering the fact that existing standard classification schemes are not suitable for the libraries which has rich collections in Hinduism. Further, this study tries to present a new depth classification scheme for Hinduism based on facet analytical approach invented by S.R. Ranganathan as a model with ability to digest further future developments and users’ perceptions on the information search in particular.